A new amphipod species of the bathyal genus Dautzenbergia Chevreux, 1900 (Amphipoda, Calliopioidea, Pontogeneiidae) associated with cold-water corals off Angola - Zettler, Michael L.; Hendrycks, Ed A.; Freiwald, André (Zootaxa, 2022)
A new species of pontogeneiid amphipod, Dautzenbergia concavipalma sp. nov., is described from cold-water corals off Angola. This is only the second observation of this genus in the South Atlantic. Important morphological characters in combination, which define the new species from its congeners, occur especially in the shape and size of gnathopod 1–2 propodus, the smooth pereopod dactyls, the shape of the basis of pereopod 7 and the telson shape with narrow cleft. The taxon is fully described and figured and is compared with known species of the genus. A key to Dautzenbergia species is also given.